Cross‐resistance to three phenylpyrazole insecticides and A2′N mutation detection of GABA receptor subunit in fipronil‐resistant Laodelphax striatellus (Hemiptera: Delphacidae). Issue 8 (6th February 2017) - Wei, Qi; Mu, Xi‐Chao; Wu, Shun‐Fan; Wang, Li‐Xiang; Gao, Cong‐Fen
Abstract: BACKGROUND: Laodelphax striatellus (Fallén) is an important pest of crops in East Asia. Over the past decade, phenylpyrazole insecticides, which target the insect GABA receptor, have increasingly been used as alternatives against rice planthoppers. RESULTS: Cross‐resistance to ethiprole and butene‐fipronil was detected in a laboratory‐selected fipronil‐resistant strain of L. striatellus (LsFR). Compared with a fipronil‐susceptible strain (LsFS), LsFR had obtained a high‐level resistance to fipronil (112.1‐fold) and moderate resistance to ethiprole (24.5‐fold) and butene‐fipronil (14.7‐fold). For the resistance of field populations, LC50 values of ethiprole were remarkably higher than the other two analogues in Gaochun and Yancheng populations in 2016. Significant correlations were demonstrated between the LC50 values of three phenylpyrazole insecticides ( R = 0.944‐0.998, P = 0.007–0.016). Additionally, an AS‐PCR assay was developed to detect the A2′N mutant GABA receptor in L. striatellus strains or populations. It was noteworthy that mutation frequencies of 19.2 and 3.6% appeared in Lujiang and Gaochun populations in 2016, respectively. Furthermore, there was an extremely significant difference in genomic expression of Lsrdl between the LsFS and LsFR individuals (1.85‐fold, F = 26.8, P = 0.0008). CONCLUSIONS: This study could help us better understand the cross‐resistance mechanisms in L. striatellus, and be beneficial for proposing effective pest management strategies of phenylpyrazole resistance. © 2016 Society of Chemical Industry